A Survey on: Comparative Study of Minimum Spanning Tree Algorithm - Gomathijayam, R; Santhi, V (International Journal of Computer Sciences and Engineering, 2025)
Minimum spanning tree can be obtained for undirected connected weighted edges with no negative weight using conventional algorithms such as genetic, Prim’s and Filter-Kruskal. This paper presents a survey on the conventional and the more recent algorithms with different techniques. This survey paper also contains comparisons of MST algorithm and their advantages and limitations.